Self-sensing coaxial muscle fibers with bi-lengthwise actuation. Issue 9 (23rd July 2021) - Dong, Lizhong; Ren, Ming; Wang, Yulian; Qiao, Jian; Wu, Yulong; He, Jianfeng; Wei, Xulin; Di, Jiangtao; Li, Qingwen
Abstract : An MXene/SWCNTs-coated CNT@PDMS coaxial muscle fiber with bi-lengthwise actuation driven by solvent to elongate and electrothermally to contract has a linear self-position sensing signal dependent on the contraction of the muscle. Abstract : Artificial muscle fibers as a promising biomimetic actuator are needed for such applications as smart soft robots, muscle function restoration, and physical augmentation. Currently developed artificial muscle fibers have shown attractive performance in contractile and torsional actuations. However, the contractile muscle fibers do not have the capability of stimulus-responsive elongation, and real-time identifying their contractile position by themselves is still challenging. We report herein the preparation of a Ti3 C2 T x MXene/single walled carbon-nanotubes (SWCNTs)-coated carbon nanotube (CNT)@polydimethylsiloxane (PDMS) coaxial muscle fiber that integrates the important features of self-position sensing and bi-lengthwise actuation. The bi-lengthwise actuation is realized by utilizing the large expansion coefficient difference of PDMS in response to solvent and heat, which results in ∼5% maximum elongation by n-heptane adsorption and ∼19% maximum contraction by electric heating under the optimal conditions. Meanwhile, due to the piezoresistive effect of the MXene/SWCNTs layer, the resistance change of this coating layer is almost linearly dependent on the contraction of the coaxial muscle fiber, providing a function of real-time self-position sensing. Furthermore, an application of using a bundle of these multifunctional coaxial muscle fibers for a bionic arm has been demonstrated, which provides new insights into the design of integrated intelligent artificial muscles with synergistic multiple functions.